ARRANGEMENT OF NATURAL DESTINATIONS TO INCREASE THE NUMBER OF TOURISTS IN LEMBANG BUNTU DATU, MENGKENDEK DISTRICT, TANA TORAJA: PENATAAN DESTINASI ALAM GUNA MENINGKATKAN JUMLAH WISATAWAN DI LEMBANG BUNTU DATU KECAMATAN MENGKENDEK, TANA TORAJA - Yohanis Lotong Ta’dung; Marinus Ronal; Jens Batara Marewa; Willy Yavet Tandirerung; Adewidar Marano Pata’dungan (Yayasan Education and Social Center, 2022)
Lembang Buntudatu is a lembang located in the Menkendek sub-district, Tana Toraja district. Therefore, the purpose of this activity is to identify the potential of the Buntu Datu Pine Forest Tourism Area based on the tourist attractions it has, and to explain the arrangement of the Buntu Datu Pine Forest Tourism Area according to its potential. The implementation method used in the activity of preparing a tourism area management plan in Lembang Buntu Datu, Mengkendek Tana Toraja District, namely the Forum Group Discussion (FGD) with the community and the management of the Buntudatu Natural Tourism Lembang, and holding workshops.The results of the discussion in this activity are developing professionalism and management patterns of Buntudatu natural tourism objects that are ready to support natural tourism activities and are able to utilize the potential of natural tourism objects in a sustainable manner. Aspects of Facilities and Infrastructure which have two sides of interest, namely (1) a tool to meet the needs of natural tourism, (2) as a control in order to maintain environmental balance, the construction of facilities and infrastructure can increase the carrying capacity so that utilization efforts can be carried out optimally